(3GdHjGf aj TQM GdOjhGf (B( (3OjhGf GdeJfHi (B)s - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYXje SdWGfg , GdLRjd EMSGfg GdhGVM HQgGfg GdPi bOQ GdCTjGA HMceJg s
(3BNQgG (B:s
(3hbO UM LejY Pdc HeG cGf CNaGg ai eOMg ai bhdg ai ZjQ gPg (B: (3heG WQHi deG QCjJc HOYI dbO cfJ CQLhG Cf CQGc aCWQH Je GdHjGf , TQM GdOjhGf , hGddg GdeSJYGf s
(3GdOjhGf eQJH Ydi GdbhGais
(3GdfSNI HgG MhGTs
(3cJHJ GdTYQ HGdMeQI HNW eLQhO s
(3Ydi MhGTji GdfSNI eJbGHdGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdCOHs